Peranan Promosi Perpustakaan Terhadap Kunjungan Pemustaka di Perpustakaan Umum Kota Solok - Afriani, Nova; Yunaldi, Yunaldi (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper aims to: (1) describe the implementation of an existing campaign to Solok City Public Library, (2) describe the constraints faced by the promotion on Solok City Public Library as well as efforts to overcome the obstacles faced by the Solok City Public Library. This paper uses descriptive method, the technique of collecting data through observation or direct observation Solok City Public Library, and interviews with the librarian at the Solok City Public Library. The findings of the promotion by Solok City Public Library has not been able to increase the interest uses to come to Solok City Public Library. It can be seen from the data end at Solok City Public Library in 2011.